How to Observe the Sun Safely - Macdonald, Lee.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
How to Observe the Sun Safely, Second Edition gives all the basic information and advice the amateur astronomer needs to get started in observing our own ever-fascinating star. Unlike many other astronomical objects, you do not need a large telescope or expensive equipment to observe the Sun. And it is possible to take excellent pictures of the Sun with today's low-cost digital cameras! This book surveys what is visible on the Sun and then describes how to record solar features and measure solar activity levels. There is also an account of how to use H-alpha and Calcium-K filters to observe and record prominences and other features of the solar chromosphere, the Sun's inner atmosphere. Because we are just entering a period of high activity on the Sun, following a long, quiet period, this is a great time to get involved with solar observing. Still emphasizing safety first, this Second Edition reflects recent and exciting advances in solar observing equipment. Chapters 6 through 8 have been completely revised to allow amateur astronomers to compare observing the Sun using digital vs. film cameras and all the latest advances in image processing. Finally, this new edition also includes more than twice as many illustrations as the first, almost half of them new images.
Preface -- Chapter 1: Our Sun -- Chapter 2: Equipment for Observing the Sun -- Chapter 3: What Can We See on the Sun? -- Chapter 4: Solar Position Measurements -- Chapter 5: Measuring Solar Activity -- Chapter 6: Observing the Chromosphere -- Chapter 7: Imaging the Sun with a Digital Camera -- Chapter 8: Webcam Imaging and Image Processing -- Appendix A: Building a Solar Projectin Box -- Appendix B: Equipment Suppliers -- Appendix C: Solar Observing Organizations -- Appendix D: Further Reading -- Index.
Keywords: Observations, Astronomical; Astronomy—Observations.; Astronomy; Astrophysics; Astronomy, Observations and Techniques; Popular Science in Astronomy; Astrophysics and Astroparticles